PERBANDINGAN KEMAMPUAN KOMUNIKASI MATEMATIS BERDASARKAN TINGKAT KEMAPUAN SISWA MELALUI PENDEKATAN PROBLEM BASED LEARNING - Amiaji Salim (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2019)
This study is aimed at analyzing students' mathematical communication skills based on the results of observations, namely the ability of junior high school students. Subjects consisted of 20 students with categories using high, medium, and low grades. The method used is the Problem Based Learning approach. Data obtained from student results because of student tests and how students in finding mathematical communication solutions students who can solve problems and can solve mathematical problems well. But few students can solve problems because students perceive that mathematics learning is very difficult, especially mathematics communication material. After the treatment of Problem Based Learning, children's results are better than classes that use normal learning. With the increase in the authors concluded that the Problem Based Learning approach can be further investigated with a lot of practice. researchers hope that the Problem Based Learning approach can add insight to students.